(untitled) (Journal of Cancer Research Updates, 2025)
Objective: This review aims to synthesize evidence on the efficacy and challenges of precision medicine strategies in cancer treatment, focusing on their role in mitigating recurrence and enhancing patient-specific therapy. Data Sources: Examination of current literature on precision medicine techniques such as immunotherapy (including checkpoint inhibitors, adoptive cell therapy, and cancer vaccines), genetic and molecular profiling for personalized treatment strategies, predictive biomarkers for selecting responsive patients, AI for improved diagnostic and prognostic accuracy, and liquid biopsies for non-invasive monitoring of minimal residual disease. Conclusion: Precision medicine in oncology offers a paradigm shift toward personalized care, potentially reducing cancer recurrence through tailored treatment modalities. While immunotherapy introduces novel mechanisms to fight cancer, its efficacy is sometimes limited by tumor evolution. Genetic and molecular profiling, along with predictive biomarkers, enable the customization of therapy plans. AI and machine learning algorithms promise to refine detection, treatment, and monitoring processes. Liquid biopsies emerge as a pivotal tool for early detection and surveillance of cancer recurrence. Further research and clinical trials are crucial for integrating these advanced strategies into standard care, aiming to enhance patient outcomes and minimize recurrence rates.